2004
DOI: 10.1177/0013916503256642
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Decisions to Volunteer in Nongovernmental Organizations

Abstract: In 1997, we surveyed members of the Appalachian Trail Conference to identify characteristics and assess motivations of the active and nonactive members in this organization. We investigated the effects of social networks, competing commitments, lifestyle changes, personal growth, and belief of the efficacy of one’s actions on decisions to become and remain active members. We found the determining factors in decisions regarding volunteer activity were competing commitments and efficacy. Active members indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 12 publications
10
74
1
Order By: Relevance
“…In addition, neither of these studies found correlations between active participation and marital status, education or employment status, whereas Koehler & Koontz (2008) found a significant correlation between participation and gender, however, Martinez & McMullin, (2004) did not. Another study conducted by Simpkins, Ripke, Huston, & Eccles (2005) reported demographic variables as predictor of youth participation in a number of out-of-school programmes.…”
Section: Antecedents Of Voluntarismmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition, neither of these studies found correlations between active participation and marital status, education or employment status, whereas Koehler & Koontz (2008) found a significant correlation between participation and gender, however, Martinez & McMullin, (2004) did not. Another study conducted by Simpkins, Ripke, Huston, & Eccles (2005) reported demographic variables as predictor of youth participation in a number of out-of-school programmes.…”
Section: Antecedents Of Voluntarismmentioning
confidence: 77%
“…Regarding income, Koehler & Koontz (2008) found no significant association to active participation; while Martinez & McMullin (2004) found that, active members actually tend to have lower incomes than those who are not active participants. Studies showed that people are considerably more likely to volunteer after a personal appeal (Martinez & McMullin, 2004;Smith, 1994).…”
Section: Antecedents Of Voluntarismmentioning
confidence: 81%
See 1 more Smart Citation
“…However, to date only a few studies have analyzed the factors impacting on the participation in environmental organizations (Mohai, 1992;Thompson and Barton, 1994;Martinez and McMullin, 2004). The advantage of focusing on direct participation in environmental organizations is that individuals' behavior can be measured.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…The age effect is now less visible, but we still observe that the AGE group [50][51][52][53][54][55][56][57][58][59] has the strongest probability of doing unpaid work and that both education and political interest have a significant and positive impact on environmental engagement. Moreover, we also observe that the "never married" individuals are the most active in environmental organizations.…”
Section: Because Evs Poses An Identical Set Of Questions To Individuamentioning
confidence: 99%